The Impact Of Exchange Rate Volatility On Financial Performance (A Systematic Literature Review) - Sebastian Sebastian (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Exchange rate volatility continues to be a critical factor affecting financial performance, particularly within emerging markets. This systematic review of the literature synthesizes 41 peer-reviewed open-access studies published from 2011 to 2025, examining the connection between exchange rate fluctuations and financial outcomes at the firm-level or sectoral scales. The findings show that most studies identify a negative impact of exchange rate volatility on profitability, stock returns, and financial stability. However, the size and direction of this relationship depend on factors like firm size, export intensity, macroeconomic variables, and institutional quality. Five major thematic areas are identified in the review: directionality of effects, sectoral heterogeneity, macro-institutional moderators, methodological innovation, and regional distribution. The literature demonstrates a methodological shift toward hybrid econometric-machine learning models. These include GARCH-MIDAS, LSTM, and Transformer architectures. This review proposes a conceptual framework. It also outlines future research agenda emphasizing comparative regional analysis, sectoral deep dives, and policy transmission mechanisms. This study contributes to the literature through offering structured synthesis and strategic roadmap. It targets researchers and policy designers focused on financial risk management in volatile currency environments.